RELATIONSHIP BETWEEN LEADERSHIP AND WORK ENVIRONMENT ON EMPLOYEE PRODUCTIVITY MEDIATED BY WORKLOAD AT PT KARYA CARMA GEMILANG (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
The success of a company is greatly influenced by the quality of its Human Resources. A company can grow rapidly if its human resources possess expertise in their respective fields. Leaders are required to help enhance employee motivation within the company, as leadership is a factor that influences the work environment. This study aims to explore more deeply whether there is a relationship between Leadership and Work Environment on Employee Productivity, mediated by Workload at PT Karya Carma Gemilang. The research method used is correlational, with a saturated sample of 49 employees of PT Karya Carma Gemilang. The results of the study show that Leadership and Workload have a positive and significant influence on Employee Productivity at PT Karya Carma Gemilang, while the Work Environment does not have an effect on productivity, and there is no influence of leadership on workload. The conclusion of this study is that better leadership and an ideal workload will result in better work productivity. The company is advised to maintain good relationships between supervisors and employees, as well as to manage an ideal workload for employees, in order to sustain employee productivity.